Benefits of the clinical pilates program in lower back pain in young handball players - Sousa, Ana Luísa (2019)
Poster presented at the 3rd International Congress of CiiEM - Research and Innovation in Human and Health Sciences. June 20-22, 2018, Campus Egas Moniz, Monte de Caparica, Portugal